Implementation of Halal Supply Chain Management in The Sea Fish Petis Food Processing Industry Putri Tunggal: Implementasi Halal Supply Chain Manajement pada Industri Pengolahan Makanan Petis Ikan Laut Putri Tunggal - Nadia Farhani (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2024)
This study aims to analyze the implementation of Halal Supply Chain Management (HSCM) in the food management industry, especially the Putri Tunggal Sea Fish Petis product. The methods used include interviews, observations, and document analysis to evaluate the process from raw material supply to distribution. The results show that the implementation of HSCM in this company is in accordance with sharia principles, including supplier selection, production processes, and packaging that meet halal standards. The analysis revealed that commitment to halal products is essential to improve competitiveness in the market. Halal certification serves not only as regulatory compliance, but also as an effective marketing strategy. With halal certification, Petis Ikan Laut Putri Tunggal can attract more consumers, especially among the Muslim community who are increasingly concerned about halal aspects in food consumption. In addition, this study highlights the importance of continuous monitoring and evaluation in maintaining halal standards. Regularly conducted internal audits help the company to ensure that all processes remain in accordance with HSCM principles. Thus, the implementation of HSCM not only increases consumer confidence but also provides a competitive advantage for Petis Ikan Laut Putri Tunggal in the local and national markets.